Too loud to talk?: Do wind turbine-related sounds affect harbour seal communication? - Lucke, Klaus; Sundermeyer, J.; Driver, J.; Rosenberger, T.; Siebert, U. (B.G. Teubner Verlag/ GWV Fachverlage GmbH Wiesbaden, 2008)
The construction of wind turbines in the offshore areas of the German North and Baltic Seas represents a grave intrusion into the habitat of harbour seals and grey seals. One of the most important aspects in this context is the emission of intense acoustic impulses during the ramming of the turbine foundations. While hearing is of secondary importance in seals for locating prey, they use acoustic signals, and hence their hearing, for communication underwater and in air. Acoustic signals are used to keep contact between mother and pups during the nursing phase as well as for territorial display and to attract mating partners. The wind turbine-related sounds could mask these signals and severely impact seals on an individual basis but also on a population level. An auditory study was conducted on trained and wild seals to provide baseline data basis for the assessment of these effects. The experiments were conducted by measuring the auditory evoked potentials (AEPs) in the seals. Subsequent to a refinement of the method an audiogram for in-air sound stimuli was measured in a trained seal at the Seal Centre in Friedrichskoog, Germany.To successfully apply this approach to wild seals, the animals had to be immobilised to avoid the strong aversive reaction of the seals to being handled. Five seal pups rehabilitated at the seal station and three free-ranging seals were tested for the hearing sensitivity. While the hearing thresholds of the trained seals were elevated at in some frequencies, the results for the wild seals are in agreement with previously published hearing data from other studies on harbour seals from the North Pacific and Atlantic. The use of previously published data on the underwater hearing sensitivity in harbour seals was therefore considered acceptable to assess the effect of wind turbine related sounds on their communication. This analysis reveals that the ramming impulses will be detectable by seals over a range of 100km and is likely to mask their communication over wide ranges, too. The potential for masking from the operational noise of wind turbines was considered to be comparably low due to its acoustic characteristics.